Michael Servetus : the unfortunate and fair conviction as heretic and seditionary at the trials in Vienne and Geneva, 1553 - Hofmeyr, J.W. (Johannes Wynand), 1947- (University of Pretoria, 2013)
Thesis (PhD (Church History))--University of Pretoria, 2007.